An ergonomics study and Rapid Upper Limb Assessments (RULA) for a car interior to support limb disabled drivers - Suliano, Salami Bahariah; Ahmad, Siti Azfanizam; As’arry, Azizan; Abdul Aziz, Faieza (Bilingual Publishing, 2022)
The demanding market shows that the need for the disabled vehicles have been increasing over the recent years. However, these factory setting cars are pricey, and its buy-sell process is time-consuming. These cars also are not meant as a universal design or inclusion design type of car, so that when it is designed for the disabled, it can be beneficial for all. With the motivation to include limbs disabled drivers in designing a universally designed car, this study aims to determine the preferred ergonomics interior of the car which can improve features needed to meet the mobility of impaired individuals in most scenarios. 5 simulations were carried out to simulate these conditions using the RULA analysis, in order to simulate the ergonomics impact on the manikin. In the final analysis, the simulations showed a virtuous score, which was between 1 and 2 for the newly redesigned interior, compared to the score of 3 to 6 for current cars. Another verification made, post questionnaire delineates positive responses upon the redesigned parts scoring 70%~90% level of ergonomics rated. Therefore, this research has set forth the necessity of redesigning a car interior and improved its ergonomic features extensively, specifically for lower limb and combined limb disabled drivers.